Nanocomposites of poly(ethylene oxide) and multiwall carbon nanotube prepared using an organic salt‐assisted dispersion technique. Issue 3 (10th August 2012) - Ratna, Debdatta; Jagtap, Siddheshwar B.; Abraham, Thomas
Abstract Poly (ethylene oxide) (PEO)/multiwall carbon nanotubes (MWCNT) nanocomposites were prepared by dispersion of MWCNTs in aqueous solution using half neutralized sodium salt of sebacic acid as a modifier. The physical interaction of half neutralized sodium salt of sebacic acid with MWCNT (cation‐π interaction) has been established by using Fourier transform infrared and Raman spectroscopic analyses. Such interaction helps in debundling the MWCNTs and resulted in a better dispersion in PEO matrix as confirmed by scanning electron microscopy and transmission electron microscopy. Addition of MWCNT significantly improves the storage modulus in rheological measurements as well as in dynamic mechanical thermal analysis. The crystallization behaviors of the composites made with the unmodified and modified MWCNTs were investigated. The modified MWCNT‐based composites shows large number of spherulite with smaller size compared to those observed in unmodified MWCNT‐based composite. POLYM. ENG. SCI. 2013. © 2012 Society of Plastics Engineers